Corrigendum to "Characterizing premixed laminar flame–acoustics nonlinear interaction" [Energy Convers. Manage. 98 (2015) 331–339]. (15th November 2015) - Zhang, Zhiguo; Guan, Di; Zheng, Youqu; Li, Guoneng
Highlights: Premixed flame–acoustics interaction is numerically studied. Premixed flame is found to respond strongly to lower-frequency perturbations. Higher-frequency flow disturbances pass through the flame smoothly. Linear and nonlinear transfer functions are determined. Hammerstein–Wiener model can provide a better agreement.